Obstacles Faced around Mathematics Education in Nepal in Terms of Promoting Meaningful, Authentic and Inclusive Education (Sotang, Yearly Peer Reviewed Journal, 2020)
In this paper, we discussed some major obstacles that are existing in promoting meaningful, authentic and inclusive education in Nepal in case of mathematics education based on the experiences and reflections gained from the study of various creations of different authors.   However, many Nepalese teachers are still using the traditional method of teaching in which a teacher is regarded as the only source of information and the learners as the vessels that need to be filled with knowledge; the modern concept of mathematics learning does not treat the students as the passive listeners as mentioned in the traditional approach. Creative learning in mathematics is the best learning approach as the demand of modern education fosters the engagement of the learners. Moreover, to make fruitful learning in mathematics with active involvement of the learners, there may arise some obstacles in our context. Therefore, this work is intended to explore the major obstacles faced around mathematics education in Nepal in terms of promoting meaningful, authentic and inclusive education. Indeed, from our in-depth study, we highlighted curriculum, pedagogical approaches, teachers’ role, evaluation process, political issues, social exclusion and location of schools as the emerging obstacles in developing meaningful, authentic and inclusive education in our context.